DEVICE FOR OBTAINING SERIES HOLOGRAPHIC INTERFEROGRAMS USING MATTE DIFFUSERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In order to expand the range of measured physical quantities, it is proposed to record a series of holographic interferograms by modulating reference beams using matte scatterers. As a result, the measurement range increased 3-4 times.
Keywords: Hologram; interferometry; high-resolution recording medium; photographic plate; laser